GRIT AND ACADEMIC PERFORMANCE AMID COVID-19 PANDEMIC: THE CASE OF THE HUMANITIES AND SOCIAL SCIENCES (HUMSS) STUDENTS - Salud, Romel (International Journal of Arts, Sciences and Education, 2022)
Recently, a study in the Philippines claimed that grittier students are more prepared for college. Nonetheless, no study has been made on the link between grit and academic achievement among Filipino senior high school (SHS) students in the current educational setup brought by the COVID-19 pandemic. Hence, using descriptive-correlational design, the study investigated the relation between grit and academic performance among 202 HUMSS students in a public SHS in Northern Philippines. The study revealed that generally, the respondents were somewhat gritty with satisfactory academic performance. Analysis showed that the respondents’ grit level significantly varies in age, sex, sibling order, grade level, parents’ highest educational attainment, employment status, and monthly net family income. Lastly, it was established that grit level is not significantly associated with academic performance.